Perception of Illness and Fear of Inhaled Corticosteroid Use among Parents of Children with Asthma - Jasna Petric Duvnjak; Emilija Lozo Vukovac; Anita Ursic; Antonela Matana; Ivana Medvedec Mikic (MDPI AG, 2023)
The most prevalent children's chronic disease worldwide is asthma which has notable negative impacts on patients' and parent's quality of life. Daily inhaled corticosteroids (ICS) therapy is a preferred controller choice. This study was conducted on 148 parents of asthmatic children to establish parents' perception of illness and fear of inhaled corticosteroids using B-IPQ and TOPICOP questionnaires. Children were in the majority male (66.9%), older than five years (58.8%), with comorbidities, and family history of atopy. Parents were female, with a mean age of 38, employed, and with a history of some form of corticosteroid use. Most parents were not afraid of ICS usage (71.6%). Unemployed parents and parents who had no medical education had a statistically significantly higher fear of using ICS (p = 0.002, p = 0.03). A child's illness affects the parents' lives and parents who are afraid of using ICS react more emotionally to the child's illness. Better understanding and less concerned about child's disease are parents of children with controlled asthma. The parents' perspective of children's asthma will affect the duration and dose of ICS treatment they will give to their children and directly influence the level of asthma control.